Matters of the hearts: Unraveling the Brand Love-Purchase Intention Nexus through a Systematic Literature Review - Gofur, Abdul; Shafariah, Hanuna (Oikonomia: Jurnal Manajemen, 2024)
Purpose This study explores the important concept of brand love and how it influences consumer behavior, especially in the context of repurchase intention. Brand love is a strong emotional bond between consumers and brands, which can influence purchasing decisions and brand loyalty. Methodology This research uses literature study with the addition of bibliometric methods to strengthen the analysis. The articles obtained for bibliometric analysis were 62 articles and the articles that had been filtered for discussion contained 3 suitable articles. Findings By understanding the relationship between brand love and repurchase intent, businesses can develop effective marketing strategies to increase consumer engagement, drive sales, and strengthen brand loyalty. Suggestion This research provides valuable insights for marketing practitioners and entrepreneurs to utilize brand love as a tool to create deep relationships with consumers and achieve sustainable competitive advantage.